Comparison of Ondansetron and Metoclopramide for the Prevention of Post-operative Nausea and Vomiting in Day-case Gynaecological Laparoscopic Surgeries - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Postoperative nausea and vomiting is a common complication following general anaesthesia for gynaecological laparoscopic procedures.Objective:This prospective study was designed to compare the efficacies of ondansetron and metoclopramide in the prevention of postoperative nausea and vomiting (PONV) after day-case gynaecological laparoscopic surgeries.Materials and Methods:Sixty-six ASA I and II consenting patients aged 18–55 years undergoing day-case gynaecological laparoscopic procedures were recruited and randomly allocated into two groups with each receiving either intravenous ondansetron 4 mg or intravenous metoclopramide 10 mg prior to the induction of anaesthesia. Nausea and vomiting were then assessed over a period of 4 hours before discharge.Results:Nausea occurred in 33.3% and 15.2% of the patients in the metoclopramide and ondansetron groups, respectively (P= 0.001). The incidence of vomiting was 9.1% and 3% (P< 0.0001) for metoclopramide and ondansetron, respectively.Conclusion:Ondansetron offered superior prophylaxis against PONV compared to metoclopramide in patients undergoing day-case gynaecological laparoscopic surgery.